The Methodology of Scholars in the Books of Contemporary Rulings Verses - Sahbaa Abdulnabi Jasim, Researcher; Morteza Al-Irwani Najafi, Prof. Dr. (lark, 2022)
Since the revelation of the Noble Qur'an to the Prophet Muhammad (PBUH), interpreting the verses of judgment in the Qur'an and understanding its intentions and meaning have been and continue to be one of the most essential subjects studied by Muslims. The time of the Companions, the Followers, and the Followers of the Followers, as well as the creation of Islamic schools of thought, until the current day. In this study, I shall investigate the methodology of two scholars who wrote in the verses of Ahl al-Bayt (peace be upon them) and Ahl al-Sunnah rulings: Sheikh Muhammad Baqir Al-Irwani gave introductory lectures on the interpretation of rulings' sections as well as a crucial study on the characteristics of the Ahl al-Bayt school of law and the duties of Imami law. In every section, the author distinguished between the fatwa (the legal ruling) and the evidence (the document) and never referenced a fatwa without evidence. In contrast, Sheikh Muhammad Ali Al-Sabouni is the second person. In his work Rawae Al-Bayan - Interpretation of Verses of Judgments from the Qur'an, Sheikh Al-Sabouni incorporated old and new compositions in terms of presentation, cohesiveness, and style. Verbal analysis with commentary and linguistics quotations. The summary of the noble verses' general meaning.
Keywords: interpretation. Verses . judgments